Polymer and preparation method thereof, gel electrolyte, energy storage device, and power utilization system
Patent Information
- Application Number
- CN202311423050.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-30
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-10-30
AI Technical Summary
目前聚合物基体通过不同的高分子单体聚合而成,但是形成的聚合物基体的综合性能较低,例如存在机械强度低,制备的凝胶电解质的低温电导率低的缺点
[0026] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention.
Smart Images

Figure CN117467086B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery material technology, specifically relating to a polymer and its preparation method, a gel electrolyte, an energy storage device, and an electrical system. Background Technology
[0002] Existing liquid electrolytes pose potential risks of combustion and leakage. Gelation is an effective means to improve safety and interfacial stability because gel polymer electrolytes utilize a polymer matrix to effectively adsorb and swell the mobile liquid electrolyte into a gel state, inheriting the high safety of all-solid-state electrolytes while combining the high conductivity of liquid electrolytes. Compared to liquid lithium-ion batteries, gel electrolytes can reduce interfacial side reactions, eliminate the need for a separator, and connect the positive and negative electrodes together, thus improving battery safety. Currently, the polymer matrix is formed by polymerizing different polymer monomers, but the overall performance of the resulting polymer matrix is relatively low, exhibiting disadvantages such as low mechanical strength and low low-temperature conductivity of the prepared gel electrolyte. Therefore, the polymer matrix of existing gel electrolytes needs improvement. Summary of the Invention
[0003] This invention aims to at least partially solve one of the technical problems in related technologies. Therefore, one object of this invention is to provide a polymer and its preparation method, a gel electrolyte, an energy storage device, and an electrical system. This polymer possesses excellent mechanical strength; using it as the polymer matrix of a gel electrolyte can improve the conductivity and mechanical strength of the gel electrolyte, thereby improving the kinetic and safety performance of the battery.
[0004] In one aspect of the invention, a polymer is provided. According to an embodiment of the invention, the polymer comprises: a polybutyl acrylate crosslinked network and a polyacrylonitrile crosslinked network, wherein the polybutyl acrylate crosslinked network and the polyacrylonitrile crosslinked network interpenetrate each other to form an interpenetrating network;
[0005] The crosslinking density of the polymer is 0.5% to 50%.
[0006] The polymer according to embodiments of the present invention includes a polybutyl acrylate crosslinking network and a polyacrylonitrile crosslinking network. The polybutyl acrylate crosslinking network and the polyacrylonitrile crosslinking network interpenetrate to form an interpenetrating network, that is, the polyacrylonitrile crosslinking network and the polybutyl acrylate crosslinking network interpenetrate to form a multilayer crosslinking network structure, thereby making the two crosslinking networks more firmly bonded and increasing the mechanical strength of the entire crosslinking network. Specifically, the crosslinking density of the polymer is 0.5% to 50%, thereby giving the polymer excellent mechanical properties. At the same time, polyacrylonitrile has high pressure resistance, and the strong network formed by the interpenetration of the polyacrylonitrile crosslinking network and the polybutyl acrylate crosslinking network further improves the electrochemical window of the polymer, thus giving the polymer even better high pressure resistance. On the other hand, the polybutyl acrylate (PB) crosslinked network has a low glass transition temperature of around -55°C. When the PB crosslinked network is above this low glass transition temperature, its molecular chains are in a highly elastic state, which is beneficial for lithium-ion conduction, thereby improving the low-temperature conductivity of the polymer gel electrolyte. Furthermore, the strong interpenetrating structure between the PB crosslinked network and the polyacrylonitrile (PAC) crosslinked network gives the polymer a higher liquid absorption rate. The polymer's excellent liquid absorption and plasticizing properties can further lower its glass transition temperature, thus improving the low-temperature conductivity of the polymer gel electrolyte. Therefore, this polymer possesses excellent mechanical strength. Using it as the polymer matrix for gel electrolytes can improve the conductivity and mechanical strength of the gel electrolyte, thereby enhancing the battery's kinetic and safety performance.
[0007] In some embodiments of the present invention, the crosslinking density of the polymer is 0.5% to 22%. As a result, the polymer has excellent mechanical strength.
[0008] In a second aspect, the present invention provides a method for preparing the above-described polymer. According to an embodiment of the present invention, the method includes:
[0009] (1) Crosslinking polymerization of butyl acrylate monomers to obtain a polybutyl acrylate crosslinked network;
[0010] (2) The polybutyl acrylate crosslinking network and acrylonitrile monomer are mixed and crosslinked to obtain a polymer.
[0011] According to the method for preparing polymers according to embodiments of the present invention, butyl acrylate monomers are first crosslinked and polymerized to form a polybutyl acrylate crosslinked network; then the polybutyl acrylate crosslinked network and acrylonitrile monomers are mixed. Since the polybutyl acrylate crosslinked network has already been formed, the acrylonitrile monomers are interspersed within the spaces of the polybutyl acrylate crosslinked network. Then the acrylonitrile monomers are crosslinked again, and the acrylonitrile monomers within the spaces of the polybutyl acrylate crosslinked network crosslink to form a polyacrylonitrile crosslinked network. The polyacrylonitrile crosslinked network and the polybutyl acrylate crosslinked network intersect each other to form a multilayer crosslinked network structure, which has superior mechanical strength compared to a single-layer crosslinked network formed by mixing and crosslinking acrylonitrile monomers and butyl acrylate monomers. Meanwhile, the polybutyl acrylate (PB) crosslinked network has a low glass transition temperature of around -55°C. When the PB crosslinked network is above this low glass transition temperature, its molecular chains are in a highly elastic state, which is beneficial for lithium-ion conduction, thus improving the low-temperature conductivity of the polymer gel electrolyte. Furthermore, the strong interpenetrating structure between the PB crosslinked network and the polyacrylonitrile (PAC) crosslinked network gives the polymer a higher liquid absorption rate. The polymer's excellent liquid absorption and plasticizing properties can further lower its glass transition temperature, thereby improving the low-temperature conductivity of the polymer gel electrolyte. Therefore, this method can prepare polymers with excellent mechanical strength. Using these polymers as the polymer matrix for gel electrolytes can improve the conductivity and mechanical strength of the gel electrolyte, thereby enhancing the battery's kinetic and safety performance.
[0012] In some embodiments of the present invention, the molar ratio of the butyl acrylate monomer to the acrylonitrile monomer is 1:(0.1 to 10). This improves the mechanical strength of the polymer.
[0013] In a third aspect, the present invention provides a method for preparing the above-described polymer. According to embodiments of the present invention, the method includes:
[0014] (1) Crosslinking polymerization of acrylonitrile monomers to obtain a polyacrylonitrile crosslinked network;
[0015] (2) The polyacrylonitrile crosslinking network and butyl acrylate monomer are mixed and crosslinked to obtain a polymer.
[0016] According to the method for preparing polymers according to embodiments of the present invention, acrylonitrile monomers are first crosslinked and polymerized to form a polyacrylonitrile crosslinked network; then, the polyacrylonitrile crosslinked network and butyl acrylate monomers are mixed. Since the polyacrylonitrile crosslinked network has already been formed, the butyl acrylate monomers are interwoven within the spaces of the polyacrylonitrile crosslinked network. Then, the butyl acrylate monomers are crosslinked again, and a polybutyl acrylate crosslinked network is formed by the mutual crosslinking of the butyl acrylate monomers within the spaces of the polyacrylonitrile crosslinked network. The polybutyl acrylate crosslinked network and the polyacrylonitrile crosslinked network interweave to form a multilayer crosslinked network structure, which has superior mechanical strength compared to a single-layer crosslinked network formed by mixing acrylonitrile monomers and butyl acrylate monomers and then crosslinking them. Meanwhile, the cross-linked network formed by the self-crosslinking of butyl acrylate monomers has a low glass transition temperature of around -55°C. When the butyl acrylate cross-linked network is above this low glass transition temperature, the molecular chains of the butyl acrylate cross-linked network are in a highly elastic state, which is beneficial for lithium-ion conduction, thereby improving the low-temperature conductivity of the polymer gel electrolyte. Furthermore, the strong interpenetrating structure between the butyl acrylate cross-linked network and the polyacrylonitrile cross-linked network gives the polymer a higher liquid absorption rate. The polymer's good liquid absorption and plasticizing properties can further lower the polymer's glass transition temperature, thus improving the low-temperature conductivity of the polymer gel electrolyte. Therefore, this method can prepare polymers with excellent mechanical strength. Using these polymers as the polymer matrix for gel electrolytes can improve the conductivity and mechanical strength of the gel electrolyte, thereby improving the battery's kinetic and safety performance.
[0017] In some embodiments of the present invention, the molar ratio of the butyl acrylate monomer to the acrylonitrile monomer is 1:(0.1 to 10). This improves the mechanical strength of the polymer.
[0018] In a fourth aspect, the present invention provides a gel electrolyte. According to embodiments of the present invention, the gel electrolyte comprises the polymer described above or a polymer prepared by the method described above. Due to the excellent mechanical properties and good overall performance of the polymer, using it as the polymer matrix of the gel electrolyte can improve the conductivity and mechanical strength of the gel electrolyte, thereby improving the kinetic and safety performance of the battery. Furthermore, the gel electrolyte has a wider electrochemical window than liquid electrolytes, not only suppressing dendrite formation but also exhibiting high-voltage resistance, further improving the cycle performance and safety performance of the battery.
[0019] In some embodiments of the present invention, the gel electrolyte has a conductivity of 10 at -20°C. -5 S / cm~10 -2 S / cm.
[0020] In some embodiments of the present invention, the tensile strength of the gel electrolyte is 0.1 MPa to 5 MPa.
[0021] In some embodiments of the present invention, the gel electrolyte further includes at least one of an electrolyte salt and a low-temperature additive.
[0022] In some embodiments of the present invention, the low-temperature additive includes at least one of dimethyl sulfoxide, methyl formate, methyl acetate, methyl butyrate and ethyl propionate, γ-butyrolactone, 1,3-propanediol cyclosulfate, fluoroethylene carbonate and vinylene carbonate. This improves the low-temperature conductivity of the gel electrolyte.
[0023] In some embodiments of the present invention, the mass percentage of the low-temperature additive is 0.1% to 5% based on the total mass of the gel electrolyte. This improves the low-temperature conductivity of the gel electrolyte.
[0024] In a fifth aspect, the present invention provides an energy storage device. According to embodiments of the invention, the energy storage device comprises the above-described gel electrolyte or a gel electrolyte prepared using the above-described method. Compared with the prior art, this energy storage device has stable safety and excellent kinetic performance under low-temperature conditions.
[0025] In a sixth aspect, the present invention provides an electrical system. According to an embodiment of the invention, the electrical system includes electrical equipment and the aforementioned energy storage device. Compared with the prior art, this electrical system has high safety and strong electrochemical performance at low temperatures.
[0026] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description
[0027] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which:
[0028] Figure 1 This is a simulation diagram of the multilayer cross-linked network structure of a polymer according to an embodiment of the present invention;
[0029] Figure 2 This is a simulation diagram of a single-layer cross-linked network structure;
[0030] Figure 3 This is an optical image of the gel electrolyte of Example 1 of the present invention;
[0031] Figure 4 This is a tensile strength test diagram of the gel electrolyte in Embodiment 1 of the present invention;
[0032] Figure 5 This is the infrared spectrum of the gel electrolyte of Example 1 of the present invention;
[0033] Figure 6 This is a tensile strength test diagram of the gel electrolyte in Embodiment 2 of the present invention;
[0034] Figure 7 This is the infrared spectrum of the gel electrolyte of Example 2 of the present invention;
[0035] Figure 8 This is the infrared spectrum of the gel electrolyte of Example 3 of the present invention. Detailed Implementation
[0036] The embodiments of the present invention are described in detail below, and are intended to explain the present invention, but should not be construed as limiting the present invention.
[0037] In one aspect of the invention, a polymer is provided. According to an embodiment of the invention, the polymer comprises: a polybutyl acrylate crosslinked network and a polyacrylonitrile crosslinked network, wherein the polybutyl acrylate crosslinked network and the polyacrylonitrile crosslinked network interpenetrate with each other to form an interpenetrating network; the crosslinking density of the polymer is 0.5% to 50%.
[0038] In this application, the test method for "crosslinking density of the polymer" is as follows: A wire mesh is weighed, with a mass of W1. An appropriate amount of interpenetrating network crosslinked polymer is weighed, with a mass of W2. Soxhlet extraction is performed using xylene as the solvent, and the wire mesh is removed after 5 hours. After the sample is dried, the wire mesh and the sample within it are weighed, and the data W3 is recorded. The crosslinking density is calculated as: Crosslinking density = [(W3-W1) / W2]·100%.
[0039] The polymer according to embodiments of the present invention includes a polybutyl acrylate crosslinking network and a polyacrylonitrile crosslinking network, wherein the polybutyl acrylate crosslinking network and the polyacrylonitrile crosslinking network interpenetrate to form an interpenetrating network, i.e., a multilayer crosslinking network structure (e.g., Figure 1 As shown), compared to the single-layer cross-linked network structure formed by polymerization (such as... Figure 2As shown), the multilayer cross-linked network structure is more robust, thereby increasing the mechanical strength of the entire cross-linked network. The specific cross-linking density of the polymer is 0.5% to 50%, preferably 0.5% to 22%. For example, it is 0.5%, 2%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc. At the same time, polyacrylonitrile has high pressure resistance, and the robust network formed by the interpenetration of the polyacrylonitrile cross-linked network and the polybutylene acrylate cross-linked network further improves the electrochemical window of the polymer, thus giving the polymer better high pressure resistance. On the other hand, the polybutyl acrylate (PB) crosslinked network has a low glass transition temperature of around -55°C. When the PB crosslinked network is above this low glass transition temperature, its molecular chains are in a highly elastic state, which is beneficial for lithium-ion conduction, thereby improving the low-temperature conductivity of the polymer gel electrolyte. Furthermore, the strong interpenetrating structure between the PB crosslinked network and the polyacrylonitrile (PAC) crosslinked network gives the polymer a higher liquid absorption rate. The polymer's excellent liquid absorption and plasticizing properties can further lower its glass transition temperature, thus improving the low-temperature conductivity of the polymer gel electrolyte. Therefore, this polymer possesses excellent mechanical strength. Using it as the polymer matrix for gel electrolytes can improve the conductivity and mechanical strength of the gel electrolyte, thereby enhancing the battery's kinetic and safety performance.
[0040] In some embodiments of the present invention, the infrared spectrum of the polymer is at 1728 cm⁻¹. -1 ~1730cm -1 It has a strong characteristic peak at 1159 cm⁻¹ for the carbonyl group C=O. -1 ~1161cm -1 It has characteristic peaks of CO antisymmetric and symmetric extensional vibrations and a peak at 1072 cm⁻¹. -1 ~1074cm -1 The out-of-plane bending vibration peak at 2240 cm⁻¹ indicates that the polymer possesses ester and alkane functional groups, thus proving the presence of acrylate polymers in the polymer structure; -1 The presence of a cyano-CN characteristic vibration peak proves that the acrylonitrile monomer has been polymerized into the polymer.
[0041] In a second aspect, the present invention provides a method for preparing the above-described polymer. According to an embodiment of the present invention, the method includes:
[0042] S1: Crosslinking polymerization of butyl acrylate monomer
[0043] In this step, butyl acrylate monomers are crosslinked and polymerized under predetermined crosslinking conditions to form a polybutyl acrylate crosslinked network. It should be noted that those skilled in the art can select the appropriate crosslinking conditions for the butyl acrylate monomers based on actual conditions. For example, radiation can be used to generate free radicals, causing the butyl acrylate monomers to crosslink themselves, or an initiator can be used to generate free radicals to initiate the crosslinking reaction.
[0044] According to embodiments of the present invention, butyl acrylate monomer, crosslinking agent, initiator, and organic solvent are mixed for crosslinking polymerization, with the molar concentration of butyl acrylate monomer being 0.1 mol / L to 5 mol / L. Controlling the molar concentration of butyl acrylate monomer to 0.1 mol / L to 5 mol / L, based on the total volume of the mixture, achieves better film formation. Further, the amount of crosslinking agent added is 1% to 20% of the mass of butyl acrylate monomer. Specifically, the crosslinking polymerization time of the butyl acrylate monomer, crosslinking agent, initiator, and organic solvent is 5 min to 24 h, thereby forming a polybutyl acrylate crosslinked network. It should be noted that the initiator and organic solvent are conventional materials in the art. Those skilled in the art can select the specific type of initiator according to the actual situation. For example, the initiator includes photoinitiators, such as 2-hydroxy-2-methylphenylacetone; or thermal initiators, such as azobisisobutyronitrile (AIBN); the organic solvent is carbonate, ether, carboxylic acid ester, etc., and the crosslinking agent includes polyethylene glycol diacrylate, benzoyl peroxide, etc.
[0045] S2: Crosslinking a polybutyl acrylate crosslinking network with acrylonitrile monomer
[0046] In this step, a polybutyl acrylate (PB) crosslinking network and acrylonitrile monomers are mixed. The acrylonitrile monomers interpenetrate within the spaces of the PB crosslinking network. Under selected crosslinking conditions, crosslinking occurs between the acrylonitrile monomers, forming a polyacrylonitrile (PAC) crosslinking network. The PAC crosslinking network formed by the acrylonitrile monomers and the PB crosslinking network interpenetrate to form a multilayer crosslinking network structure. This structure exhibits superior mechanical strength compared to a single-layer crosslinking network formed by mixing and crosslinking acrylonitrile monomers and PB monomers. Simultaneously, the PB crosslinking network has a low glass transition temperature of approximately -55°C. When the PB crosslinking network is above this low glass transition temperature, the molecular chains of the PB crosslinking network are in a highly elastic state, which is beneficial for lithium-ion conduction, thereby improving the low-temperature conductivity of the polymer gel electrolyte. Furthermore, the strong interpenetrating structure of the PB crosslinking network and the PAC crosslinking network gives the polymer a higher liquid absorption rate. The polymer's excellent liquid absorption and plasticizing properties can further lower the polymer's glass transition temperature, thus improving the low-temperature conductivity of the polymer gel electrolyte. It should be noted that those skilled in the art can select the crosslinking conditions for the polybutyl acrylate crosslinking network and the acrylonitrile monomer mixture.
[0047] According to embodiments of the present invention, a polybutyl acrylate crosslinking network is mixed and crosslinked with acrylonitrile monomer, a crosslinking agent, an initiator, and an organic solvent. Free radicals are generated by the initiator, causing the acrylonitrile monomer to crosslink, forming a polyacrylonitrile crosslinking network. Specifically, the crosslinking time for the polybutyl acrylate crosslinking network with the acrylonitrile monomer, crosslinking agent, initiator, and organic solvent is 5 min to 48 h. Further, based on the volume of the mixed acrylonitrile monomer, crosslinking agent, initiator, and organic solvent, the molar concentration of the acrylonitrile monomer is 0.1 mol / L to 5 mol / L. The amount of crosslinking agent added is 1% to 20% of the mass of the acrylonitrile monomer.
[0048] According to embodiments of the present invention, the molar ratio of butyl acrylate monomer to acrylonitrile monomer is 1:(0.1-10). The inventors have discovered that the molar ratio of butyl acrylate monomer to acrylonitrile monomer added during polymer formation has a significant impact on the mechanical properties of the polymer. Specifically, if the molar ratio of butyl acrylate monomer to acrylonitrile monomer is too large or too small, it is not conducive to the formation of a uniform interpenetrating network structure. Therefore, this application uses a molar ratio of butyl acrylate monomer to acrylonitrile monomer of 1:(0.1-10) to prepare the polymer, which can improve the mechanical strength of the polymer.
[0049] Therefore, this method can be used to prepare polymers with excellent mechanical strength. Using these polymers as the polymer matrix for gel electrolytes can improve the conductivity and mechanical strength of the gel electrolytes, thereby improving the kinetic and safety performance of the battery.
[0050] In a third aspect, the present invention provides a method for preparing the above-described polymer. According to embodiments of the present invention, the method includes:
[0051] S10: Crosslinking polymerization of acrylonitrile monomer
[0052] In this step, acrylonitrile monomers are crosslinked and polymerized under predetermined crosslinking conditions to form a polyacrylonitrile crosslinked network. It should be noted that those skilled in the art can select the crosslinking conditions for acrylonitrile monomers based on actual conditions. For example, acrylonitrile monomers, crosslinking agents, initiators, and organic solvents can be mixed for crosslinking polymerization. Specifically, the crosslinking polymerization time for acrylonitrile monomers, crosslinking agents, initiators, and organic solvents is 5 min to 24 h, thereby forming a polyacrylonitrile crosslinked network. Further, based on the total volume of the mixed acrylonitrile monomers, crosslinking agents, initiators, and organic solvents, the molar concentration of acrylonitrile monomers is 0.1 mol / L to 5 mol / L.
[0053] S20: Crosslinking a polyacrylonitrile crosslinking network with butyl acrylate monomer.
[0054] In this step, the polyacrylonitrile crosslinking network and butyl acrylate monomer are mixed and crosslinked. Since the polyacrylonitrile crosslinking network has already been formed, the butyl acrylate monomer is interwoven within the spaces of the polyacrylonitrile crosslinking network. Then, the butyl acrylate monomer undergoes further crosslinking. The polybutyl acrylate crosslinking network formed by the butyl acrylate monomer crosslinking and the polyacrylonitrile crosslinking network interweave to form a multilayer crosslinking network structure. Compared with the single-layer crosslinking network formed by mixing acrylonitrile monomer and butyl acrylate monomer and then crosslinking, this structure has superior mechanical strength. Simultaneously, the crosslinking network formed by the butyl acrylate monomer itself has a low glass transition temperature of approximately -55°C. When the polybutyl acrylate crosslinking network is above this low glass transition temperature, the molecular chains of the polybutyl acrylate crosslinking network are in a highly elastic state, which is beneficial for lithium-ion conduction, thereby improving the low-temperature conductivity of the polymer gel electrolyte. Furthermore, the strong interpenetrating structure of the polybutyl acrylate crosslinking network and the polyacrylonitrile crosslinking network gives the polymer a higher liquid absorption rate. The polymer's good liquid absorption and plasticizing properties can further lower the polymer's glass transition temperature, thereby improving the low-temperature conductivity of the polymer gel electrolyte. It should be noted that those skilled in the art can select the appropriate crosslinking conditions based on the mixing of the polyacrylonitrile crosslinking network and the butyl acrylate monomer. Further, the polyacrylonitrile crosslinking network is mixed and crosslinked with the butyl acrylate monomer, crosslinking agent, initiator, and organic solvent. Free radicals are generated by the initiator, causing the butyl acrylate monomer to crosslink and form a polybutyl acrylate monomer crosslinking network. Based on the total volume of the mixed butyl acrylate monomer, crosslinking agent, initiator, and organic solvent, the molar concentration of the butyl acrylate monomer is 0.1 mol / L to 5 mol / L. Specifically, the crosslinking time for the polyacrylonitrile crosslinking network and the butyl acrylate monomer, crosslinking agent, initiator, and organic solvent is 5 min to 48 h.
[0055] According to embodiments of the present invention, the molar ratio of butyl acrylate monomer to acrylonitrile monomer is 1:(0.1-10). The inventors have discovered that the molar ratio of butyl acrylate monomer to acrylonitrile monomer added during polymer formation has a significant impact on the mechanical properties of the polymer. Specifically, if the molar ratio of butyl acrylate monomer to acrylonitrile monomer is too large or too small, it is not conducive to the formation of a uniform interpenetrating network structure. Therefore, this application uses a molar ratio of butyl acrylate monomer to acrylonitrile monomer of 1:(0.1-10) to prepare the polymer, which can improve the mechanical strength of the polymer.
[0056] Therefore, this method can be used to prepare polymers with excellent mechanical strength. Using these polymers as the polymer matrix for gel electrolytes can improve the conductivity and mechanical strength of the gel electrolytes, thereby improving the kinetic and safety performance of the battery.
[0057] In a fourth aspect, the present invention provides a gel electrolyte. According to embodiments of the present invention, the gel electrolyte comprises the polymer described above or a polymer prepared using the method described above. Due to the excellent mechanical properties and good overall performance of the polymer, using it as the polymer matrix of the gel electrolyte can improve the conductivity and mechanical strength of the gel electrolyte, thereby improving the kinetic and safety performance of the battery. Furthermore, the gel electrolyte has a wider electrochemical window than the liquid electrolyte, not only suppressing dendrite formation but also exhibiting high-voltage resistance, further improving the cycle performance and safety performance of the battery.
[0058] According to an embodiment of the present invention, the conductivity of the gel electrolyte at -20°C is 10. -5 S / cm~10 -2 S / cm. For example, conductivity is 1.10. -5 S / cm, 1·10 -4 S / cm, 5·10 -4 S / cm, 1·10 -3 S / cm, 5·10 -3 S / cm, 1·10 -2 S / cm, etc.
[0059] According to embodiments of the present invention, the tensile strength of the gel electrolyte is 0.1 MPa-5 MPa, for example 0.3 MPa, 0.5 MPa, 0.8 MPa, 1 MPa, 1.5 MPa, 2 MPa, 2.5 MPa, 3 MPa, 3.5 MPa, 4 MPa, 4.5 MPa, 5 MPa, etc.
[0060] According to embodiments of the present invention, the gel electrolyte further includes at least one of an electrolyte salt and a low-temperature additive. Further, the low-temperature additive includes at least one of dimethyl sulfoxide, methyl formate, methyl acetate, methyl butyrate and ethyl propionate, γ-butyrolactone, 1,3-propanediol cyclosulfate, fluoroethylene carbonate and vinylene carbonate, thereby improving the low-temperature conductivity of the gel electrolyte.
[0061] Specifically, when the prepared battery is a lithium-ion battery, the electrolyte salt may include at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, or lithium tetrafluorooxalate phosphate. When the prepared battery is a sodium-ion battery, the electrolyte sodium salt may include at least one of sodium hexafluorophosphate, sodium difluorooxalate borate, sodium tetrafluoroborate, sodium bis(oxalate borate), sodium perchlorate, sodium hexafluoroarsenate, sodium bis(fluorosulfonyl)imide, sodium trifluoromethanesulfonate, or sodium bis(trifluoromethanesulfonyl)imide.
[0062] According to embodiments of the present invention, the mass percentage of the low-temperature additive is 0.5% to 5% based on the total mass of the gel electrolyte. The inventors have found that controlling the mass percentage of the low-temperature additive within the above range based on the total mass of the gel electrolyte can reduce the interfacial impedance of the battery and improve the low-temperature conductivity of the gel electrolyte. Therefore, when the mass percentage of the low-temperature additive is 0.5% to 5% based on the total mass of the gel electrolyte, the gel electrolyte prepared in this application exhibits superior low-temperature performance.
[0063] According to one embodiment of the present invention, the method for preparing the above-mentioned gel electrolyte includes:
[0064] S100: Crosslinking polymerization of butyl acrylate monomer, crosslinking agent, solvent and electrolyte salt.
[0065] In this step, butyl acrylate monomer, crosslinking agent, solvent, and electrolyte salt are mixed and crosslinked to obtain a polybutyl acrylate electrolyte salt crosslinked network. It should be noted that the solvent uses materials conventional in the art, which can be selected by those skilled in the art according to actual needs. For example, the solvent includes at least one of propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl acrylate, ethyl acetate, propyl acetate, methyl propionate, propyl propionate, ethyl butyrate, 1,4-butyrolactone, and ethylene glycol dimethyl ether. Furthermore, those skilled in the art can select specific crosslinking conditions according to actual needs. For example, butyl acrylate monomer, crosslinking agent, solvent, electrolyte salt, and initiator are mixed and crosslinked to polymerize, with the initiator generating free radicals to crosslink the butyl acrylate monomer.
[0066] S200: A crosslinking process involving a polybutyl acrylate electrolyte salt crosslinking network, acrylonitrile monomer, crosslinking agent, solvent, and electrolyte salt.
[0067] In this step, the polybutyl acrylate electrolyte salt crosslinking network, acrylonitrile monomer, crosslinking agent, solvent, and electrolyte salt are mixed. At this stage, the mixing of acrylonitrile monomer, crosslinking agent, solvent, and electrolyte salt is a simple physical mixing; the acrylonitrile monomer does not undergo a polymerization reaction. The acrylonitrile monomer interpenetrates within the polybutyl acrylate electrolyte salt crosslinking network, and then the acrylonitrile monomer crosslinks again. The network structure formed by the crosslinking of acrylonitrile monomer interpenetrates with the polybutyl acrylate electrolyte salt crosslinking network, while the electrolyte salt also interpenetrates within the crosslinked polyacrylonitrile (PAC) crosslinking network, thus giving the gel electrolyte excellent mechanical strength. On the other hand, the crosslinking network formed by the butyl acrylate monomer itself has a low glass transition temperature of around -55°C. At temperatures above this low glass transition temperature, the molecular chains of the polybutyl acrylate crosslinking network are in a highly elastic state, which is beneficial for lithium ion conduction, thereby improving the low-temperature conductivity of the gel electrolyte. Furthermore, the strong interpenetrating structure of the polybutyl acrylate crosslinking network and the PAC crosslinking network gives the polymer a higher liquid absorption rate. The polymer's good liquid absorption and plasticizing properties can further lower the polymer's glass transition temperature, thereby improving the low-temperature conductivity of the gel electrolyte.
[0068] According to another embodiment of the present invention, a method for preparing the above-mentioned gel electrolyte includes:
[0069] Sa: Crosslinking polymerization of acrylonitrile monomer, crosslinking agent, solvent and electrolyte salt.
[0070] In this step, acrylonitrile monomers, crosslinking agents, solvents, and electrolyte salts are mixed and crosslinked to obtain a polyacrylonitrile electrolyte salt crosslinked network. It should be noted that the crosslinking agents, solvents, and electrolyte salts are conventional materials in the art, and those skilled in the art can select them according to actual needs, for example, referring to the above. Furthermore, those skilled in the art can select specific crosslinking conditions according to actual needs; for example, acrylonitrile monomers, crosslinking agents, solvents, electrolyte salts, and initiators can be mixed and crosslinked to generate free radicals through the initiator, causing the acrylonitrile monomers to crosslink.
[0071] Sb: A crosslinking process involving a polyacrylonitrile electrolyte salt crosslinking network, butyl acrylate monomer, crosslinking agent, solvent, and electrolyte salt.
[0072] In this step, the polyacrylonitrile electrolyte salt crosslinking network, butyl acrylate monomer, crosslinking agent, solvent, and electrolyte salt are mixed. At this stage, the mixing of butyl acrylate monomer, crosslinking agent, solvent, and electrolyte salt is a simple physical mixing; the butyl acrylate monomer does not undergo a polymerization reaction. The butyl acrylate monomer interpenetrates between the polyacrylonitrile electrolyte salt crosslinking network, and then the butyl acrylate monomer crosslinks again. The network structure formed by the crosslinking of butyl acrylate monomer interpenetrates with the polyacrylonitrile electrolyte salt crosslinking network, while the electrolyte salt also interpenetrates between the crosslinked polybutyl acrylate crosslinking networks. This results in the gel electrolyte having excellent mechanical strength. Simultaneously, the crosslinking network formed by the butyl acrylate monomer itself has a low glass transition temperature of approximately -55°C. At temperatures above this low glass transition temperature, the molecular chains of the polybutyl acrylate crosslinking network are in a highly elastic state, which is beneficial for lithium-ion conduction, thus improving the low-temperature conductivity of the gel electrolyte. Furthermore, the strong interpenetrating structure of the polybutyl acrylate crosslinking network and the polyacrylonitrile crosslinking network gives the polymer a higher liquid absorption rate. The polymer's good liquid absorption and plasticizing properties further lower the polymer's glass transition temperature, thereby improving the low-temperature conductivity of the gel electrolyte.
[0073] In a fifth aspect, the present invention provides an energy storage device. According to embodiments of the present invention, the energy storage device includes the above-described gel electrolyte or a gel electrolyte prepared using the above-described method. Compared with the prior art, this energy storage device has stable safety and excellent kinetic performance under low-temperature conditions. It should be noted that the energy storage device may include, but is not limited to, single-cell batteries, battery modules, battery packs, battery systems, etc. The actual application form of the energy storage device provided in the embodiments of this application may be, but is not limited to, the listed products, and may also be other application forms. The embodiments of this application do not strictly limit the application form of the energy storage device.
[0074] In a sixth aspect, the present invention provides an electrical system. According to embodiments of the invention, the electrical system includes an electrical device and the aforementioned energy storage device. Compared with the prior art, this electrical system offers high safety and strong electrochemical performance at low temperatures. For example, the electrical device can include, but is not limited to, portable electronic devices such as mobile phones, tablets, laptops, desktop computers, smart bracelets, smartwatches, e-readers, and game consoles. It can also be used in vehicles such as automobiles, trucks, cars, freight cars, bullet trains, high-speed trains, and electric vehicles. Furthermore, it can also be used in various household appliances, such as refrigerators, lights, and air conditioners.
[0075] The present invention will now be described with reference to specific embodiments. It should be noted that these embodiments are merely descriptive and do not limit the present invention in any way.
[0076] Example 1
[0077] (1) 3g of butyl acrylate (BA) monomer, 0.02g of photoinitiator (2-hydroxy-2-methylphenylacetone), 0.1g of polyethylene glycol diacrylate and 5g of solvent (N,N-dimethylformamide) were mixed and then subjected to free radical polymerization under UV light for 30min to obtain a polybutyl acrylate crosslinked network.
[0078] (2) The polybutyl acrylate crosslinked network obtained in step (1), 1g of acrylonitrile monomer, 0.02g of photoinitiator (2-hydroxy-2-methylphenylacetone), 0.1g of polyethylene glycol diacrylate and 5g of solvent (N,N-dimethylformamide) were mixed and subjected to free radical polymerization under UV irradiation for 30min to obtain a polymer. Its infrared spectrum showed a value of 1728cm. -1 1159cm -1 1074cm -1 Characteristic peaks at wavenumber; wherein the molar ratio of butyl acrylate monomer to acrylonitrile monomer is 6:5, the solvent is dried to obtain interpenetrating polymer, and the crosslinking density of the polymer is 22.0%.
[0079] (3) Battery manufacturing
[0080] a. Preparation of positive electrode sheet: The positive active material (lithium iron phosphate), conductive agent (acetylene black), and binder (polyvinylidene fluoride) are mixed evenly in an appropriate amount of solvent N-methylpyrrolidone (NMP) at a mass ratio of 90:5:5 to obtain a positive electrode slurry. The positive electrode slurry is coated on the positive current collector aluminum foil, and the positive electrode sheet is obtained through drying, cold pressing, slitting, and cutting processes.
[0081] b. Preparation of negative electrode sheet: The negative electrode active material (graphite), conductive agent (acetylene black), binder (styrene-butadiene rubber) and sodium carboxymethyl cellulose are mixed evenly in an appropriate amount of deionized water at a mass ratio of 94.5:2.5:1.5:1.5 to obtain a negative electrode slurry. The negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through drying, cold pressing, slitting and cutting processes.
[0082] c. The separator is made of polyethylene film. The positive electrode, separator and negative electrode are stacked in sequence and then wound to obtain the electrode assembly. The electrode assembly is placed in the outer packaging. The prepared polymer and 1g of electrolyte salt solution (lithium hexachlorophosphate concentration is 1mol / L) are mixed and injected into the dried battery to obtain the battery. The polymer and 1g of electrolyte salt solution are mixed to obtain gel electrolyte.
[0083] Example 2
[0084] (1) 1g of butyl acrylate (BA) monomer, 0.02g of photoinitiator (2-hydroxy-2-methylphenylacetone), 0.1g of polyethylene glycol diacrylate and 5g of solvent (N,N-dimethylformamide) were mixed and then subjected to free radical polymerization under UV light for 30min to obtain a polybutyl acrylate crosslinked network.
[0085] (2) The polybutyl acrylate crosslinking network obtained in step (1), 1g of acrylonitrile monomer, 0.02g of photoinitiator (2-hydroxy-2-methylphenylacetone), 0.1g of polyethylene glycol diacrylate and 5g of solvent (N,N-dimethylformamide) were mixed and subjected to free radical polymerization under UV irradiation for 30min to obtain a polymer. Its infrared spectrum showed a value of 1729 cm⁻¹. -1 1161cm -1 1074cm -1 Characteristic peaks at wavenumber; wherein the molar ratio of butyl acrylate monomer to acrylonitrile monomer is 2:5, the solvent is dried to obtain an interpenetrating polymer, and the crosslinking density of the polymer is 10.1%.
[0086] (3) The preparation process of the battery in Example 2 is the same as that in Example 1. The main difference is that the polymer and 4g of electrolyte salt solution are mixed and injected into the dried battery to obtain the battery. The polymer and 4g of electrolyte salt solution are mixed to obtain a gel electrolyte.
[0087] Example 3
[0088] (1) 0.5g acrylonitrile (AN) monomer, 0.02g photoinitiator (2-hydroxy-2-methylphenylacetone), 0.1g polyethylene glycol diacrylate and 5g solvent (N,N-dimethylformamide) were mixed and then subjected to free radical polymerization under UV light for 30 min to obtain a polyacrylonitrile crosslinked network.
[0089] (2) The polyacrylonitrile crosslinked network obtained in step (1), 1g of butyl acrylate monomer, 0.02g of photoinitiator (2-hydroxy-2-methylphenylacetone), 0.2g of polyethylene glycol diacrylate and 5g of solvent (N,N-dimethylformamide) were mixed and subjected to free radical polymerization under UV irradiation for 30min. After drying, the polymer was obtained, and its infrared spectrum showed a value of 1729cm. -1 1159cm -1 1074cm -1 Characteristic peaks at wavenumber; wherein the molar ratio of butyl acrylate monomer to acrylonitrile monomer is approximately 4:5, the solvent is dried to obtain an interpenetrating polymer with a crosslinking density of 7.8%.
[0090] (3) The preparation process of the battery in Example 3 is the same as that in Example 1. The main difference is that the polymer and 7g electrolyte salt solution are mixed and injected into the dried battery to obtain the battery. The polymer and 7g electrolyte salt solution are mixed to obtain a gel electrolyte.
[0091] Example 4
[0092] (1) 2g acrylonitrile (AN) monomer, 0.02g photoinitiator (2-hydroxy-2-methylphenylacetone), 0.3g polyethylene glycol diacrylate and 5g solvent (N,N-dimethylformamide) were mixed and then subjected to free radical polymerization under UV light for 30min to obtain a polyacrylonitrile crosslinked network.
[0093] (2) The polyacrylonitrile crosslinked network obtained in step (1), 1g of butyl acrylate monomer, 0.02g of photoinitiator (2-hydroxy-2-methylphenylacetone), 0.2g of polyethylene glycol diacrylate and 5g of solvent (N,N-dimethylformamide) were mixed and subjected to free radical polymerization under UV irradiation for 30min to obtain a polymer. Its infrared spectrum showed a value of 1729 cm⁻¹. -1 1159cm -1 1074cm -1 Characteristic peaks at wavenumber; wherein the molar ratio of butyl acrylate monomer to acrylonitrile monomer is approximately 1:5, the solvent is dried to obtain an interpenetrating polymer, and the crosslinking density of the polymer is 15.5%.
[0094] (3) The preparation process of the battery in Example 4 is the same as that in Example 1. The main difference is that the polymer and 14g electrolyte salt solution are mixed and injected into the dried battery to obtain the battery. The polymer and 14g electrolyte salt solution are mixed to obtain a gel electrolyte.
[0095] Example 5
[0096] (1) 3g of butyl acrylate (BA) monomer, 0.02g of photoinitiator (2-hydroxy-2-methylphenylacetone), 0.1g of polyethylene glycol diacrylate and 0.5g of electrolyte (containing 1mol / L lithium hexafluorophosphate, ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) = 1:1:2 (volume ratio), electrolyte additives) were mixed and then subjected to free radical polymerization under UV light for 30min to obtain a polybutyl acrylate electrolyte salt crosslinking network.
[0097] (2) The polybutyl acrylate electrolyte salt crosslinking network obtained in step (1), 0.124 g acrylonitrile monomer, 0.02 g photoinitiator (2-hydroxy-2-methylphenylacetone), and 0.5 g electrolyte (containing 1 mol / L lithium hexafluorophosphate, EC:EMC:DMC = 1:1:2 (volume ratio), and electrolyte additives) were mixed and subjected to free radical polymerization under UV irradiation for 30 min to obtain a gel electrolyte; its infrared spectrum showed a 1728 cm⁻¹. -1 1159cm -1 1074cm -1 The characteristic peak at the wavenumber; wherein the molar ratio of butyl acrylate monomer to acrylonitrile monomer is 10:1.
[0098] (3) The difference between the preparation process of the battery in Example 5 and Example 1 is that the gel electrolyte obtained in step (2) is injected into the dried battery.
[0099] Example 6
[0100] (1) 3g of butyl acrylate (BA) monomer, 0.02g of photoinitiator (2-hydroxy-2-methylphenylacetone), 0.1g of polyethylene glycol diacrylate and 0.5g of electrolyte (containing 1mol / L lithium hexafluorophosphate, EC:EMC:DMC=1:1:2 (volume ratio), electrolyte additives) were mixed and then subjected to free radical polymerization under UV light for 30min to obtain a polybutyl acrylate electrolyte salt crosslinking network.
[0101] (2) The polybutyl acrylate electrolyte salt crosslinking network obtained in step (1), 1g acrylonitrile monomer, 0.02g photoinitiator (2-hydroxy-2-methylphenylacetone) and 0.5g electrolyte (containing 1mol / L lithium hexafluorophosphate, EC:EMC:DMC = 1:1:2 (volume ratio), electrolyte additives) were mixed and subjected to free radical polymerization under UV irradiation for 30min to obtain a gel electrolyte; its infrared spectrum showed a 1728cm⁻¹. -1 1159cm -1 1074cm -1 The characteristic peak at the wavenumber indicates that the molar ratio of butyl acrylate monomer to acrylonitrile monomer is 6:5.
[0102] (3) The difference between the preparation process of the battery in Example 6 and Example 1 is that the gel electrolyte obtained in step (2) is injected into the dried battery.
[0103] Example 7
[0104] (1) 3g of butyl acrylate (BA) monomer, 0.02g of photoinitiator (2-hydroxy-2-methylphenylacetone), 0.1g of polyethylene glycol diacrylate and 0.5g of electrolyte (containing 1mol / L lithium hexafluorophosphate, EC:EMC:DMC=1:1:2 (volume ratio), electrolyte additives) were mixed and then subjected to free radical polymerization under UV light for 30min to obtain a polybutyl acrylate electrolyte salt crosslinking network.
[0105] (2) The polybutyl acrylate electrolyte salt crosslinking network obtained in step (1), 1.24 g acrylonitrile monomer, 0.02 g photoinitiator (2-hydroxy-2-methylphenylacetone) and 0.5 g electrolyte (containing 1 mol / L lithium hexafluorophosphate, EC:EMC:DMC = 1:1:2 (volume ratio), electrolyte additives) were mixed and subjected to free radical polymerization under UV irradiation for 30 min to obtain a gel electrolyte; its infrared spectrum showed a 1728 cm⁻¹. -1 1159cm -1 1074cm -1 The characteristic peak at the wavenumber indicates that the molar ratio of butyl acrylate monomer to acrylonitrile monomer is 1:1.
[0106] (3) The difference between the preparation process of the battery in Example 7 and Example 1 is that the gel electrolyte obtained in step (2) is injected into the dried battery.
[0107] Example 8
[0108] (1) 3g of butyl acrylate (BA) monomer, 0.02g of photoinitiator (2-hydroxy-2-methylphenylacetone), 0.1g of polyethylene glycol diacrylate, 0.5g of electrolyte (containing 1mol / L lithium hexafluorophosphate, EC:EMC:DMC=1:1:2 (volume ratio), electrolyte additives) and 0.05g of low-temperature additive (dimethyl sulfoxide) were mixed and then subjected to free radical polymerization under UV irradiation for 30min to obtain a polybutyl acrylate electrolyte crosslinking network.
[0109] (2) The polybutyl acrylate electrolyte salt crosslinking network obtained in step (1), 1g acrylonitrile monomer, 0.02g photoinitiator (2-hydroxy-2-methylphenylacetone), and 0.5g electrolyte (containing 1mol / L lithium hexafluorophosphate, EC:EMC:DMC = 1:1:2 (volume ratio), as well as 0.2g dimethyl sulfoxide and 0.05g vinyl chloride (VC) as electrolyte low-temperature additives) were mixed and subjected to free radical polymerization under UV irradiation for 30min to obtain a gel electrolyte; its infrared spectrum showed a 1728cm⁻¹. -1 1159cm -1 1074cm -1 Characteristic peaks at wavenumber.
[0110] (3) The main difference between the preparation process of the battery in Example 8 and Example 1 is that the gel electrolyte obtained in step (2) is injected into the dried battery.
[0111] Comparative Example 1
[0112] (1) 1g of butyl acrylate (BA) monomer, 0.02g of photoinitiator (2-hydroxy-2-methylphenylacetone (HMPP)), 0.06g of polyethylene glycol diacrylate (PEGDA), and 5g of solvent (N,N-dimethylformamide) were mixed evenly and subjected to free radical polymerization under UV irradiation to obtain a milky white polymer. Its infrared spectrum showed a wavelength of 1729 cm⁻¹. -1 1252cm -1 1159cm -1 Characteristic peaks at wavenumber.
[0113] (2) A precursor solution was prepared by uniformly mixing 1g of butyl acrylate (BA) monomer, 0.02g of photoinitiator (2-hydroxy-2-methylphenylacetone (HMPP)), 3g of electrolyte (containing 1mol / L lithium hexafluorophosphate, EC:EMC:DMC = 1:1:2 (volume ratio), and electrolyte additives), and 0.06g of polyethylene glycol diacrylate (PEGDA). Free radical polymerization was then carried out under UV irradiation to obtain a milky white, soft PBA cross-linked network gel electrolyte. Its infrared spectrum showed a wavelength of 1729 cm⁻¹. -1 1252cm -1 1159cm -1 Characteristic peaks at wavenumber. The resulting gel electrolyte is injected into the dried battery.
[0114] Comparative Example 2
[0115] (1) A precursor solution was prepared by uniformly mixing 1g of acrylonitrile (AN) monomer, 0.02g of photoinitiator (2-hydroxy-2-methylphenylacetone (HMPP)), 1g of polyethylene glycol diacrylate (PEGDA), and 5g of solvent (N,N-dimethylformamide). Free radical polymerization was then carried out under UV light to obtain a yellow polymer. After drying the solvent, the polymer showed an infrared signature of 2240 cm⁻¹. -1 Small peaks in wavenumber.
[0116] (2) 1g of acrylonitrile (AN) monomer, 0.02g of photoinitiator (2-hydroxy-2-methylphenylacetone (HMPP)), 3g of electrolyte (containing 1mol / L lithium hexafluorophosphate, EC:EMC:DMC = 1:1:2 (volume ratio), electrolyte additives), and 1g of polyethylene glycol diacrylate (PEGDA) were mixed evenly to form a precursor solution. Free radical polymerization was then performed under UV irradiation to obtain a yellow PAN cross-linked network gel electrolyte, which showed an infrared signature of 2240 cm⁻¹. -1The wavenumber peaks were observed. The resulting gel electrolyte was injected into the dried battery.
[0117] Comparative Example 3
[0118] (1) Mix 1g of acrylonitrile (AN) monomer, 1g of butyl acrylate (BA) monomer, 0.02g of photoinitiator (2-hydroxy-2-methylphenylacetone (HMPP)), 1g of polyethylene glycol diacrylate (PEGDA) and 5g of solvent (N,N-dimethylformamide) evenly, and then perform free radical polymerization under UV light and dry to obtain P(AN-BA) single network polymer.
[0119] (2) 1g of acrylonitrile (AN) monomer, 1g of butyl acrylate (BA) monomer, 0.02g of photoinitiator (2-hydroxy-2-methylphenylacetone (HMPP)), 3g of electrolyte (containing 1mol / L lithium hexafluorophosphate, EC:EMC:DMC = 1:1:2 (volume ratio), electrolyte additives), and 1g of polyethylene glycol diacrylate (PEGDA) were mixed evenly to form a precursor solution. Under UV irradiation, free radical polymerization was performed in one step to obtain a P(AN-BA) monolayer gel electrolyte. The obtained gel electrolyte was then injected into a dried battery.
[0120] The low-temperature conductivity, tensile strength, and oxidation potential of the gel electrolytes prepared in Examples 1-8 and Comparative Examples 1-3 were measured using the following methods:
[0121] Low-temperature conductivity testing: A blocking battery of model 2016 was fabricated and stored in a low-temperature chamber for 2 hours before AC impedance testing. Ionic conductivity was calculated using the formula: conductivity (σ) = electrolyte thickness (L) / resistance (Rs) × cross-sectional area (S).
[0122] Tensile strength: Tested using a universal tensile testing machine. First, the gel electrolyte was dried and cut into strips of 5cm x 1.5cm. The thickness d (in μm) was measured. These strips were then clamped on the tensile testing machine at a tensile speed of 100mm / min. Tensile strength = maximum tensile force at break / cross-sectional area. The cross-sectional area is the product of the strip width and the electrolyte thickness d.
[0123] Oxidation potential: Oxidation potential is an important indicator of the electrochemical stability of an electrolyte, reflecting its ability to resist oxidation. It is measured by linear sweep voltammetry (LSV). The electrolyte is sandwiched between stainless steel sheets and encapsulated in a coin cell, serving as a blocking cell. The voltage range for LSV measurement is 0–6 V, with a scan rate of 0.5 mV / s (for solid-state electrolytes) or 5 mV / s (for liquid electrolytes).
[0124] The low-temperature conductivity, tensile strength, and oxidation potential of the gel electrolytes prepared in Examples 1-8 and Comparative Examples 1-3 were measured, and the specific results are shown in Table 1.
[0125] Table 1
[0126]
[0127] The crosslinking densities of the polymers in Examples 1-4 all ranged from 0.5% to 50%, indicating that these polymers possess excellent mechanical properties. Furthermore, as shown in Table 1, the conductivity and tensile strength at -20°C of the gel electrolytes in Examples 1-8 were significantly higher than those in Comparative Examples 1-3, demonstrating that the gel electrolytes prepared using the polymers of this application possess excellent mechanical properties and conductivity. Simultaneously, the gel electrolytes in Examples 1-8 also exhibited higher oxidation potentials, thereby suppressing dendrite formation and improving battery safety.
[0128] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0129] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a polymer, characterized in that, include: (1) The butyl acrylate monomer, crosslinking agent, initiator and organic solvent are mixed and crosslinked to obtain a polybutyl acrylate crosslinked network; (2) The polybutyl acrylate crosslinking network and acrylonitrile monomer are mixed and crosslinked to obtain a polymer; In this process, the total volume of the mixture of butyl acrylate monomer, crosslinking agent, initiator, and organic solvent is used as the basis, the molar concentration of the butyl acrylate monomer is 0.1 mol / L to 5 mol / L, and the crosslinking polymerization time is 5 min to 24 h. or, The method includes: (1) Acrylonitrile monomer, crosslinking agent, initiator and organic solvent are mixed and crosslinked to obtain a polyacrylonitrile crosslinked network; (2) The polyacrylonitrile crosslinking network and butyl acrylate monomer are mixed and crosslinked to obtain a polymer; In this process, based on the total volume of acrylonitrile monomer, crosslinking agent, initiator, and organic solvent, the molar concentration of acrylonitrile monomer is 0.1 mol / L to 5 mol / L, and the crosslinking polymerization time is 5 min to 24 h. The polymer comprises a polybutyl acrylate crosslinked network and a polyacrylonitrile crosslinked network, wherein the polybutyl acrylate crosslinked network and the polyacrylonitrile crosslinked network interpenetrate to form an interpenetrating network; the crosslinking density of the polymer is 7.8%~22%. The molar ratio of butyl acrylate monomer to acrylonitrile monomer is 1:(0.1~10).
2. A gel electrolyte, characterized in that, This includes polymers prepared using the method described in claim 1.
3. The gel electrolyte according to claim 2, characterized in that, The gel electrolyte must satisfy at least one of the following conditions: The conductivity at -20℃ is 10. -5 S / cm~10 -2 S / cm; and The tensile strength of the gel electrolyte is 0.1 MPa to 5 MPa.
4. The gel electrolyte according to claim 2 or 3, characterized in that, It also includes a low-temperature additive, which includes at least one of dimethyl sulfoxide, methyl formate, methyl acetate, methyl butyrate and ethyl propionate, γ-butyrolactone, 1,3-propanediol cyclosulfate, fluoroethylene carbonate and vinylene carbonate.
5. The gel electrolyte according to claim 4, characterized in that, Based on the total mass of the gel electrolyte, the mass percentage of the low-temperature additive is 0.1% to 5%.
6. An energy storage device, characterized in that, Includes the gel electrolyte according to any one of claims 2-5.
7. An electrical system, characterized in that, The energy storage device includes the one described in claim 6.
Citation Information
Patent Citations
Novel gel polymer electrolyte with interpenetrating network structure and preparation method and application thereof
CN102522589A